2011
DOI: 10.1371/journal.pone.0014424
|View full text |Cite
|
Sign up to set email alerts
|

Barcoding a Quantified Food Web: Crypsis, Concepts, Ecology and Hypotheses

Abstract: The efficient and effective monitoring of individuals and populations is critically dependent on correct species identification. While this point may seem obvious, identifying the majority of the more than 100 natural enemies involved in the spruce budworm (Choristoneura fumiferana – SBW) food web remains a non-trivial endeavor. Insect parasitoids play a major role in the processes governing the population dynamics of SBW throughout eastern North America. However, these species are at the leading edge of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 63 publications
3
82
0
Order By: Relevance
“…This is encouraging, as studies from other sites and biotopes are needed to confirm our hostspecificity analysis and they are likely to be very informative even if they do not have the resources to include both morphological and molecular species concept evidence. It also corroborates Kaartinen et al (2010) and Smith et al (2011) who showed that added molecular evidence for parasitoids had a low impact on food web parameters.…”
Section: Host Specificity Of Parasitoid Groupssupporting
confidence: 86%
“…This is encouraging, as studies from other sites and biotopes are needed to confirm our hostspecificity analysis and they are likely to be very informative even if they do not have the resources to include both morphological and molecular species concept evidence. It also corroborates Kaartinen et al (2010) and Smith et al (2011) who showed that added molecular evidence for parasitoids had a low impact on food web parameters.…”
Section: Host Specificity Of Parasitoid Groupssupporting
confidence: 86%
“…The current results thus imply that the molecular methods are complementary, and that in future studies, traditional techniques such as rearing should (at the very least) be supported by these faster and less laborious molecular methods (but see SI Text, section 4 for further considerations). By determining the identity of the host (or prey) from the gut contents of the parasitoid (or predator) (30,35,61,62), and/or by directly identifying the parasitoid DNA from the host (36), molecular approaches also circumvent problems associated with the detection of the feeding event (e.g., [63][64][65], or the maturation of the parasitoid (66,67). Given the wide availability of PCR and the rapid advances in sequencing techniques, methods for detecting both hosts within parasitoids and parasitoids within hosts based on DNA barcodes is now an approach within reach for all ecologists (34,43).…”
Section: Discussionmentioning
confidence: 99%
“…Besides sequencing methodology, recent studies have expanded upon prey identification techniques to compare predator diet breadth and composition over time and across different habitats Razgour et al 2011). Further applications include revealing the prey of locally threatened species (Murray et al 2011), identifying natural predators of an economically important pest (Smith et al 2011), characterizing the microbial communities within the predators themselves (Scupham et al 2007), and quantifying prey consumption via real-time PCR techniques (Bowles et al 2011). Besides arthropod prey, molecular techniques were used to tease apart plant diets of herbivores via fecal samples enabling the separation of foraging niches (Corse et al 2010;Valentini et al 2009).…”
Section: Discussionmentioning
confidence: 99%